Letter to Dr. Nathan T. Wolkomir from Homer R. Hoisington - Homer R. Hoisington:::::: (1973)
A letter sent to Dr. Nathan T. Wolkomir, the president of the NFFE, from Homer R. Hoisington, the regional business agent of the NFFE, describing the move to replace 1450 employees in Point Mugu Naval Base with private contractors.